Formulasi Masker Gel Antioksidan Mengandung Ekstrak Kulit Buah Naga Merah (Hylocereus polyrhizus) - Sunarmi Sunarmi; Susilo Yulianto (Poltekkes Kemenkes Surakarta, 2017)
Abstract: Antioxidant, Red Dragon Fruit, Gel Mask. Skin is an organ that covers the entire human body, which has protection against external influences. Free radicals and the oxidation reaction can be inhibited by an antioxidant compound. Red dragon fruit peel is rarely used but has high antioxidant activity that can be used for skin care, especially facial skin. Red dragon fruit peel can be formulated into various dosage form of antioxidants for the face skin, one of which peel-off mask gel. This study aimed to test the antioxidant activity of peel-off mask gel with the active ingredient of red dragon fruit peel extracts. This research uses experimental methods. Red dragon fruit peel extracted by maceration in 70% ethanol and concentrated. Gel mask made in 3 variations extract concentration, ie formula A, B and C 0.175 g, 0.350 g and 0,700 g respectively. The physical stability test was conducted by cycling test for 6 cycles. The physical properties of the preparation were tested before and after storage include adhesion, dispersive power, pH, viscosity and time to dry. Antioxidant activity tested with DPPH method. Based on test results obtained physical stability, third-formula gel mask physically qualified and stable, except for the dispersive power. Antioxidant activity decreased after the storage. The highest activity was shown by formula C with an IC50 value of 3497.113 ppm. Based on IC50 values, this gel mask has an inactive. antioxidant activity.